Artificial salmon tracking algorithm: Preliminary designing approach for optimizing the integrated mixed energy composition - Afandi, A.N.; Fadlika, Irham; Sias, Quota Alief; Rahmawati, Y.; Lestari, D.; Handayani, A.N.; Sulistyorini, Yunis; Farrel, C.W.A.; Michiko, R.S.A. (MATEC web of conferences, 2018)
Recently, an energy mix providing becomes an important problem to face unsustainable energy sources fuelled by coal derivation. The optimal composition between various energy sources also leads to the generated portion of the unit commitment. By considering this issues, these works are subjected to find out the optimal scheduled production of the energy mix throughout an optimization problem considered conventional and renewable energy sources. Moreover, these studies also introduce Artificial Salmon Tracking Algorithm for carrying out the problem. By considering technical requirements, results show that the total energy mixing is produced dynamically to feed the hourly demand. The contribution of the conventional and renewable energy sources affect to discharged pollutants.